2017
DOI: 10.7166/28-3-1861
|View full text |Cite
|
Sign up to set email alerts
|

High Cycle Fatigue Properties of as-Built Ti6al4v (Eli) Produced by Direct Metal Laser Sintering

Abstract: The high cycle fatigue (HCF) properties of direct metal laser sintering (DMLS) of Ti6Al4V (ELI) in three mutually orthogonal build directions were investigated by cycling specimens under load control, in a tension-tension fatigue testing machine. Semi-log graphs of maximum stress (S) against life (N) of the specimens produced along the respective three build directions were plotted, and the displayed endurance limits compared. Optical and scanning electron microscopy were used to compare and analyse the crack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
2
7
2
Order By: Relevance
“…The fatigue data of these specimens are presented in Figure 2. These fatigue results showed characteristics similar to the curve profile for Ti6Al4V(ELI) observed by Malefane et al [14] on machined test specimens. A comparison between the X-and Y-direction specimens showed no significant effect of the layer orientation on the fatigue performance.…”
Section: Fatigue Properties Of Ti6al4v(eli) Test Specimens Produced Through Lpbfsupporting
confidence: 87%
See 1 more Smart Citation
“…The fatigue data of these specimens are presented in Figure 2. These fatigue results showed characteristics similar to the curve profile for Ti6Al4V(ELI) observed by Malefane et al [14] on machined test specimens. A comparison between the X-and Y-direction specimens showed no significant effect of the layer orientation on the fatigue performance.…”
Section: Fatigue Properties Of Ti6al4v(eli) Test Specimens Produced Through Lpbfsupporting
confidence: 87%
“…In the study of Malefane et al [14], the vertically built specimens showed a shorter fatigue life than the horizontal specimens owing to the effect of internal defects (entrapped sub-surface gas pores) that were inherent in the LPBF process. In the current study, specimens X8 and Y7 could reach an endurance limit of 5 million cycles at 190 MPa, while the Z8 specimen reached the limit at the maximum stress of 225 MPa.…”
Section: Figure 3: Gauge Length Of Lpbf Ti6al4v Test Specimen Built In X-directionmentioning
confidence: 99%
“…Extrapolation of the linearised curve for the fractured specimens and the horizontal curve for the fatigue endurance limit at = 450 MPa resulted in an estimate of the knee point at 55,690,000 load cycles, as indicated in Figure 2. This knee point estimate is higher than the estimated value for the as-built X-build direction DMLS Ti6Al4V (ELI) specimens in reference [16] and assumed here during testing. This implies an increase in the number of load cycles to failure of DMLS Ti6Al4V (ELI) specimens after the application of the HTA process [16].…”
Section: Tensile Properties Of High Temperature Annealed Dmls Ti6al4vcontrasting
confidence: 58%
“…This knee point estimate is higher than the estimated value for the as-built X-build direction DMLS Ti6Al4V (ELI) specimens in reference [16] and assumed here during testing. This implies an increase in the number of load cycles to failure of DMLS Ti6Al4V (ELI) specimens after the application of the HTA process [16]. Table 5 shows the values of the maximum tension-tension fatigue stresses and the corresponding number of load cycles to failure or run-out of the test specimens.…”
Section: Tensile Properties Of High Temperature Annealed Dmls Ti6al4vcontrasting
confidence: 58%
See 1 more Smart Citation